MOLECULAR CHARACTERIZATION OF M. PHASEOLINA AND ITS MANAGEMENT USING AGROCHEMICALS AND T. HARZIANUM - K. A. Sido; W. A. Hassan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Systemic Acquired Resistance (SAR) induced by agrochemicals of chitosan (CH) and salicylic acid (SA) at (25, 50 and 100 ppm) , in addition to a biocontrol agent of T. harzianum (Th) at 4 ×106 were examined against M. phaseolina the causal agent of charcoal rot of sunflower. The results depended on estimation of diseases severity and microsclerotia density in the soil. Thus, the seeds immersion in CH 75 ppm for 6 h., gave the highest and considerable reduction (p=0.05) in disease severity by 48.25% and reduced microsclerotia survived in the soil up to 70%. Application of SA at 50 and 75 ppm proved an obvious reduction of charcoal rot severity by up to 39% and 37% for both concentrations, respectively and not varied with Th. The results also confirmed that CH at 75 ppm revealed significant reduction 40.63% in disease severity and similarized with SA at same concentration. However, the lowest dose of SA at 25 ppm realized the highest reduction of micro sclerotia density by 80.28 % compared to 74.91% when used CH at 75 ppm. For molecular identification of a pathogen Polymerase Chain Reaction (PCR) using ITS4 and ITS5 universal primers were applied to amplify and sequence of DNA for six isolates of M. phaseolina viz., OL901219, OL636051, OL901220, OL901204, OL636050 and OL636053 compared for identity of rDNA sequence according to NCBI GenBank databases by BLAST mode and the results showed the entire similarity ratio reached to 100%